GAMBARAN KELUHAN MUSKULOSKELETAL DISORDERS (MSDS) PADA PEKERJA UD.X TAHUN 2021 - Norus Sholeha; Merry Sunaryo (Jurnal Kesehatan Masyarakat (Undip), 2022)
UD. X is an industry engaged in the convection of making wallets manually with a total of 7 workers. After direct observation, there are potential hazards that cause the risk of occupational diseases (PAK), namely musculoskeletal disorders (MSDs). Musculoskeletal disorders (MSDs) are complaints of pain in certain body parts experienced by workers. The purpose of this study is to find out the description of the complaints of musculoskeletal disorders (MSDs) suffered by the workers. This study uses an analytical method using a Nordic Body Map (NBM) questionnaire. The results showed that 5 workers experienced moderate levels of complaints and 2 workers experienced high levels of complaints. In addition, the body parts that often experience pain/pain are the upper neck, back, waist, buttocks and right calf. Complaints of musculoskeletal disorders (MSDs) have occurred in all workers at PT. X with a complaint rate of almost 71.4% being. Suggestions that can be given are redesigning the workplace that is adjusted to the worker's height when sitting or standing, replacing existing chairs with more ergonomic chairs, requiring workers to stretch before work and providing supporting facilities such as PPE (earplugs) and first aid kits.